HucMSCs can alleviate abnormal vasculogenesis induced by high glucose through the MAPK signaling pathway - Yang Yao; Tiantian Shan; Xiaoying Li (iScience)
Summary: Vascular complications caused by diabetes mellitus contribute a major threat to increased disability and mortality of diabetic patients, which are characterized by damaged endothelial cells and angiogenesis. Human umbilical cord-derived mesenchymal stem cells (hucMSCs) have been demonstrated to alleviate endothelial cell damage and improve angiogenesis. However, these investigations overlooked the pivotal role of vasculogenesis. In this study, we utilized blood vessel organoids (BVOs) to investigate the impact of high glucose on vasculogenesis and subsequent angiogenesis. We found that BVOs in the vascular lineage induction stage were more sensitive to high glucose and more susceptible to affect endothelial cell differentiation and function. Moreover, hucMSCs can alleviate the high glucose-induced inhibition of endothelial cell differentiation and dysfunction through MAPK signaling pathway downregulation, with the MAPK activator dimethyl fumarate further illustrating the results. Thereby, we demonstrated that high glucose can lead to abnormal vasculogenesis and impact subsequent angiogenesis, and hucMSCs can alleviate this effect.